Uji Formulasi Spray Scant Diffuse Untuk Memanipulasi Bau Tubuh - setia budi; Melviani Melviani (Fakultas Farmasi Universitas Setia Budi, 2022)
A person's activities are often disturbed by the presence of body odor which can affect self-confidence and social interaction. The use of body fragrances cannot reduce or overcome body odor, so that there is a need for new preparations that can neutralize body odor and bind and break down odors. The type of food consumed can affects body odor and can also be influenced by hormones. The body odor presence as the result of sweat processed by the normal flora on the skin. Bacteria such as the Corynebacterium group, Propionibacterium group, and Staphylococcus epidermidis play a role in the occurrence of body odor. Other bacteria that cause body odor are Staphylococcus aureus, Pseudomonas aeruginosa, and Streptococcus pyogenes. Combination of Scant Diffuse Formulation (antibacterial) with hydrogen peroxide (antimicrobial), activated carbon (odor binding), and sodium bicarbonate (bacterial metabolism inhibitor), is expected to be solution to get rid of body odor. The research focus is to determined the stability of the preparation, with use and storage evaluation criteria. Methods the research itself uses the evaluation test stage of laboratory pre-experimental spray preparations, namely the one-shoot case study by looking at the organoleptic test, viscosity, storage stability, degree of inertia, and homogeneity, and stability. Results In organoleptics, there was sedimentation in formulations 2 and 3, which made it difficult to disperse and could be re-dispersed when shaken strongly. Stable spray preparation is in formula 1 with a concentration of active substances, namely 20 mg sodium bicarbonate and 2 mg active carbon.